Pengaruh Arus Kas Operasi, Leverage dan Ukuran Perusahaan Terhadap Manajemen Laba (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016 -2019) - Reta Eka Sari; Maulana Malik Muhammad (UNIVERSITAS KALBIS, 2022)
The aim of this research is to provide empirical evidence about the effect of operating cash flow, leverage, and company size on earnings management. The population this research are manufacturing companies listed in Indonesia Stock Exchange period 2016-2019. The samples of this study are 195 data using proposive sampling method. The data analysis method used in this research is multiple regression analysis using SPSS version 25. The result of this research show that operating cash flow has positive effect on earnings management and company size has negative effect on earnings management. But leverage has no effect on earnings management.